Performance of 6 Different Global Navigation Satellite System Receivers at Low Latitude Under Moderate and Strong Scintillation. Issue 2 (19th February 2021) - de Paula, E. R.; Martinon, A. R. F.; Moraes, A. O.; Carrano, C.; Neto, A. C.; Doherty, P.; Groves, K.; Valladares, C. E.; Crowley, G.; Azeem, I.; Reynolds, A.; Akos, D. M.; et al.
Abstract: After sunset, in the equatorial regions ionospheric plasma irregularities are generated due to the generalized Rayleigh‐Taylor instability. Under favorable conditions these irregularities develop in the equatorial region while mapping along the magnetic field lines giving rise to large plasma depletion structures called Equatorial Plasma Bubbles with embedded smaller structures on their walls. The global navigation satellite system (GNSS) L1 band frequency is sensitive to irregularities of the size of 300–400 m in the first Fresnel zone, which cause scattering and diffraction of the signal and produce amplitude and/or phase scintillation. Severe scintillation of GNSS signals can in turn cause loss of lock of the receiver code and/or carrier loops. As a result, GNSS navigation and positioning solution can be adversely affected by the ionospheric scintillation. There are multiple GNSS receivers designed to monitor scintillations. These receivers are based on different hardware designs and use different methodologies to process the raw data. When using simultaneous data from different GNSS scintillation monitors it is important to evaluate and compare their performances under similar scintillation conditions. The scintillation monitoring techniques may be useful for many applications that use GNSS signal. The aim of this work is to evaluate the performance of six different GNSS receivers located at São José dos Campos (23.1°S, 45.8°W, dip latitude 17.3°S) during moderate and strong scintillation activity. The amplitude (S4 ) and phase (σϕ ) scintillation indexes from these receivers were analyzed and compared for the nights February 20–21 and November 27–28, 2013. Key Points: Description of six scintillation monitors and their scintillation indexes processing methodologies are presented Performance of six different global navigation satellite system receivers is analyzed during moderate and strong ionospheric scintillation When calculating the phase scintillation index phase, cycle slips, and data gaps were detected and repaired before detrending the carrier phase